COMPARATIVE EFFECT BETWEEN QUESTION ANSWER RELATIONSHIP AND DIRECTED READING THINKING ACTIVITY TECHNIQUES ON READING COMPREHENSION - ., PUTU WIWIN SUPANDENI; ., Prof. Dr. I Nyoman Sudiana, M.Pd; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
This study is an experimental study on the tenth year students of Saraswati Senior High School Seririt in the academic year 2012/2013, which aimed to investigate whether there is (1) Is there an interactional effect through teaching narrative and descriptive text using QAR techniques and DRTA techniques of the first year students of SMA Saraswati Seririt; 2) Is there significant difference on the students? reading competency who were taught by using QAR and DRTA techniques in narrative text of the first year student of SMA Saraswati Seririt in the academic year of 2012/2013; 3) Is there significant difference in students? reading comprehension between Question Answer; 4) Is there an interactional effect through teaching narrative and descriptive text using QAR techniques and DRTA techniques of the first year students of SMA Saraswati Seririt. In analyzing the data 2X2 factorial design was used and involved 140 students as sample. The data were collected through reading test and analyzed by Two-way ANOVA. Research?s result indicates that (1) there is a significant interactional effect between the teaching techniques applied and text types; (2) there is a significant difference in reading achievement between students who are taught by using QAR technique and those taught by using DRTA technique in descriptive text type; and (3) there is a significant difference in reading achievement between the students who are taught by using QAR technique and those taught by using DRTA technique in narrative text type; (4) there is a significant difference in reading achievement between the students who are taught by using QAR technique and those taught by using DRTA technique. Key words: comparative, QAR, DRTA, reading achievement INTRODUCTION language as a means of communication is constructed of elements; sounds, words, and sentences presented in the form symbols used to express ideas, feelings, and thoughts. This language perspective comes nearly toward the language teaching which is primarily concerned with second or foreign learning. By applying the language learning appropriately, human could be able to express the ideas, feelings, and thoughts in a real communication, make relation each other. Each member of society will then recognize one another within their community, family, tribes, regency, nation, and daily activities (Dinnen (1967). Moreover, there are four language skills which should be mastered by students in learning English. Those four language skills are listening, speaking, reading, and writing. From those language skills mentioned above, reading skill should be mastered by students. Through reading, students can enlarge their knowledge and experiences. Having good ability in reading, the students can understand written text in the target language. In supporting this insight, Harmer (2007) highlights that English teacher should understand the importance of reading skill in supporting students English competence. He discloses that reading is useful for language acquisition. Teacher?s main task is provide the students more or less understand what they read, the more they read, the better they get at it. Reading also has positive effect on students? vocabulary knowledge, on their spelling and on their writing. Harmer adds that reading skill also provide good models for English writing, encourage student to focus on vacabulary, grammar or punctuation. In line with Harmer?s concept, Olson and Ames (1972) stated that reading has a very important role in learning process because the skill of reading very much determines the success of the students in learning many things particularly in daily life. Without the skill of reading, they cannot make satisfactory progress in school. Moreover, reading is an important skill that must be thought by the teacher because through reading, students are expected to be able to get more about certain knowledge, information and pleasure. To achieve reading comprehension, there are several important components that the students should master. Furthermore, Walker (2008) says that reading skill has always been an essential part of English as a Foreign Language (EFL). In EFL setting, EFL students may not use English in their environment, and they just learn English in formal situation. By read some English texts may help the EFL students in acquiring their target language. In this case, reading skill is very important for the students especially for EFL students in mastering English language. However, reading is a cognitive process in which not only about spelling a word by words or mastering vocabulary, but also readers have to construct their creative thinking by combining their prior knowledge, their previous experiences, and their situation with the information, idea, and the situation of the written text that they read in order to comprehend the textual, ideational meanings, and the values of the texts. Additionally, Paris (2005) also affirms that reading is one of the greatest accomplishments for the language learners because it is the foundation for learning and academic achievement. He adds that developing reading skill is an important component in learning a language, by reading, the students could enrich their vocabulary, because by reading some texts, the readers will try hard to get the meaning about the text, so the readers have to understand every word that they read. More than that reading skill is to be highly provided to be mastered by students in terms of comprehending the English text. Anne Ediger in Celce-Murcia (2001: 153) affirms that reading seems to be primary to the most skills because the teaching of writing and oral skills is increasingly being integrated with reading instruction for EFL learners. Further, Ediger highlights that reading can be gradually being recognized as a valuable source of language input, particularly for students in learning environments in which fluent speakers of English are generally not available to provide other kinds of language input. Besides, Nunan (1991) emphasizes that reading is a complex and purposeful socio-cultural, cognitive, and linguistic process in which readers simultaneously use their knowledge of spoken and written language, their knowledge of the topic of the text. They also use of their knowledge about their culture to construct meaning with the text. This means that reading is a process of relating to the knowledge of the readers with the ideas in the text to construct meaning. It is also a process of making sense of the text by decoding the written symbols. The importance of reading skill cannot be denied. The components can be categorized as the basic competencies that the students should achieve, they are: 1) the ability to obtain general and specific information from the written text, either it is explicitly or implicitly stated, 2) the ability to obtain main ideas stated in a text whether explicitly or implicitly, 3) the ability to guess the meaning of the words, phrases, or sentences based on the context, and 4) the ability to understand reference devices used in a text (Depdiknas, 2007). Consequence of this description, in Indonesia, English becomes a primary subject that is taught in school. Until now, learning English is developed widely from elementary level to university level. It is supported by the government by always developing the national curriculum to become better. As stated in Depdiknas (2007) that KTSP is an operational curriculum which is constructed and implemented by each educational unit. In other words, KTSP (specifically English curriculum) is signified by the realization of local autonomy in educational field in which one of the elements is the students? ability to read as the determinant of the speed of learning process. It means that the learning process should be emphasized on the implementation of reading skill, without ignoring the other skills. As a matter of fact, the teaching of reading in schools seemed to fail to equip students with reading skills that needed in real life. The real life reading skills in this context refer to students? ability to efficiently find information from a brochure, or other authentic materials. To be able to gain the skills, the teaching of reading should be innovative and is closed to real life context. However, it was found that many teachers still applied conventional technique in their teaching learning process, in which the students were mainly assigned to read the passage and then work on questions related to those passages. In other words, there had been a convention that a class was always started with reading the passage and continued by answering the questions. Therefore, it is necessary to find other technique which can optimize the factors which can influence students? reading comprehension as well as develop their reading skills. The students? inability to understand English? reading comprehension is caused by inside and outside factors. The inside factors are students? learning motivation, age, aptitude, learning style. Meanwhile, the outside factor is related to the teacher?s technique in creating good classroom atmosphere. The teacher should be able to recognize the students? problem and to create conducive atmosphere in the classroom that will raise the students? competency to understand reading comprehension. Consequently, English teachers are expected to apply the appropriate technique which will surely work to fulfill learners? need of reading comprehension. Related to this assumption, Richards and Rodgers (1987:12) said that teaching is usually regarded as something that teachers do in order to bring about changes in learners. A central component of methodology is how teachers view their role in the process. The teacher?s role is to active the students in learning. In teaching, teacher helps the students to find their own ways in learning. In further comprehending of the teacher?s role, Breen and Candlin as quoted by Richard and Rodgers (1987:77) stated that teacher?s role is to facilitate communication process between all participants in the classroom, and between these participants. Teacher should creatively a communication atmosphere in the classroom. In supporting ideas of fulfilling learners? need of reading comprehension as described above, English teachers are hoped to choose appropriate techniques in their teaching learning process. Related to this idea, question answer relationships (QAR) and directed reading thinking activity (DRTA) are good to be implemented. According to Raphael (1986) defines that Question-Answer Relationship (QAR) is a way to help students to figure out how to get about answering-questions based on a given text. This strategy will help them to understand the different types of question and know how to approach the text based on the different questions types effectively and efficiently. The three components of question-answer relationship (QAR) strategy are right there question, think and search question, author and you questions, and on my own question Helping students to analyze the question-answer will enable them to become skillfull in analyzing the types of question that they are typically asked to respond to when reading a text. Further Raphael discloses the reasons of implementing QAR in teaching reading comprehension; 1) question-answer relationship technique helps students learn the kind of thinking that different types of questions require, as well as where to go for answers in the text. It encourages students to be more efficient and strategic readers, 2) question-answer relationship can help students to ask effective questions as they read and respond to the text, 3) Teachers use QAR to guide and monitor student learning and to promote higher-level thinking in their students. Besides, Conner (2006) highlights that Question-Answer Relationship (QAR)) as a reading strategy in which students categorize comprehension question according to where they get information they need to answer each question. The students are asked to indicate whether the information they use to answer question about the text is textually explicit and implicit information. Conner adds his logical reasons for the strength points of the possibility in implementing the QAR in teaching reading in EFL teaching, that is, it helps the students figure out how to go about answering the questions based on a given text and it helps students understanding the different types of question and know to approach requires the students to analyze the types of question. Furthermore, Zygouris-Coe and Glass (2004) affirms that QAR technique helps students better understanding of the text learned. Moreover, Walker (1992) states that there are nine steps followed to apply QAR technique in teaching reading such as: 1) The teacher selects a text that represents different kinds of questions, 2) The introduce ?right there? sources of information. ?Right there? means that the answers are ?right there? on the page and the words from the text can be used to answer the question. This source must often be used in answering a teacher?s question and in in completing textbook exercise. The teacher completes an example lesson identifying the kind of answer that is required by the questions as well as the answer. She models the strategy of finding answers to questions and identifying the sources of information used, 3)The teacher introduces the ?think and search? question answer relationship. Here, the students must read the text carefully and then ?think and search? different parts of the text to find the answers that fit together to answer the question, 4) Then, the teacher introduces ?author and you? sources of information. In this response, the students need to think about what they know, what the author tells them, and how this information fit together, 5) The teacher completes an example lesson, identifying the kind of answer that is required by the questions as well as the answer. She models by using all four sources of information and telling why and how the answers were obtained, 6) The students complete a third example lesson using a paragraph, the question, and the answer. The students as a group identify the question-answer relationship. The students talk about reasons for a particular answer and strategy used to obtain the answer, 7) The students complete fourth example lesson using a paragraph, the question, and the answers. Individually, the students identify the question-answer relationship. Then, the students tell why they choose answer, based on the textual and non textual information and the strategy used to obtain the answer, and 8) Steps 5,6, and 7 are extended to longer passages in progressive steps until the procedure can be used with basal readers or content area text. Meanwhile, Stauffer (1980) says that the Directed Reading-Thinking Activity is considered as a framework that can be especially effective in content area reading. He also considers the DRTA, which is often used in conjunction with basal readers, as an aid for students in overcoming some of the problems associated with content area materials, such as difficulty in understanding highly technical and unfamiliar concepts, seeing a need or purpose for reading the material under consideration, dealing with content material at a readability level above the student?s ability, and handling content area material independently. Further, Burgess (1997) also states that: DRTA is a group type reading activity in which all members of group type read at the same time. The primary objective is to develop a skill in reading critically. Predictions, assumption, and problem solving are important features in the approach. Burgess discloses steps in teaching reading by using DRTA such as: 1) Use the index or table of contents to have students predict what they think story tells about and what they like to find out, 2) Use title and first picture for setting the purpose, 3) Use some of the story?s pictures without the title, 4) Read to the end the first page or second page or middle of the story and allow students to set their purpose for reading, 5) Read one-fourth or some fraction of the story, then another fraction, and another. At the end of each section the students stop reading and refine their purposes, 6) Read last page of the story first, and 7) Use key vocabulary words. More than that Burgess highlights strategies for developing reading omprehension in a group setting in terms of DRTA technique such as: 1) Ask students about what their ?going? to read. This enhances higher level thinking rather than asking them what they have read which encourages literal recall, 2) Minimize ?no? answer from teacher. Instead ask students to share why they believe what they believe, 3) Do not accept ?I don?t know? answers. Encourage students to make their best guess, 4) Make sure you give adequate time for students to formulate answers and do not allow more aggressive students to dominate. Give at least five seconds wait time after asking question and express that you would like to hear from certain students, 5) Avoid diversionary question, 6) Encourage students to listen to other students, 7) Minimize paraphrasing. If the teacher paraphrases the responses, students will listen less effectively to their peers and expect that teacher will sharpen or modify the responses. This lessens the students? participation in the thinking process, 8) Make sure that students understand that a good response is based on using the evidence from the reading passage, not whether they are ?right? or ?wrong?, and 9) Create an open and trusting environment. Addressing QAR and DRTA technique as stated above, the study supposed to answer four questions, namely: (1) whether there is a significant difference in reading achievement between students who are taught by using QAR technique and those taught by using DRTA technique; (2) whether there is a significant interactional effect between teaching techniques applied and two text types; (3) whether there is a significant difference in reading achievement between students who are taught by using QAR technique and those taught by using DRTA technique in descriptive text type; and (4) whether there is a significant difference in reading achievement between students who are taught by using QAR technique and those taught by using DRTA technique in narrative text type. The undertaking as such aimed at (1) finding out whether there is a significant difference in reading achievement between students who are taught by using QAR technique and those taught by using DRTA technique; (2) finding out whether there is a significant interactional effect between teaching techniques applied and two text types; (3) finding out whether there is a significant difference in reading achievement between students who are taught by using QAR technique and those taught by using DRTA technique in descriptive text type; and (4) finding out whether there is a significant difference in reading achievement between students who are taught by using QAR technique and those taught by using DRTA technique in narrative text type. RESEARCH METHODS This research conducted at the second semester of the tenth grade students of Saraswati Senior High School Seririt, this reserach was done in two months (March ? April). There were five classes of tenth grades students as the population of this study, which altogether consisted of 175 students. Sample of 140 students was used, which was selected by using Random Sampling Technique. By doing the lottery, two classes as experimental groups and two classes as control groups was selected and then the experimental groups were taught by using QAR technique both descriptive and narrative text types and control groups were taught by the DRTA technique both descriptive and narrative text types. The research used a posttest only control group design by using a 2 x2 factorial arrangement. Two classes as experimental group were taught by using QAR technique, which one class taught by using descrptive text type and one class taught by using narrative text type and two classes as control group were taught by using DRTA technique, which one class taught by using descrptive text type and one class taught by using narrative text type. There were three variables in this research, that is, independent variable (QAR and DRTA techniques), moderator variable (descriptive and narrative text types), and dependent variable (reading achievement). The data were collected by using a reading comprehension test in multiple choice type. This instrument had been tried out to measure their validity and reliability. To collect this data the students were asked to answer 30 item numbers based on instruction given on test paper. Furthermore, the test was constructed based on the reading dimmensions. Data analysis was conducted after obtaining the scores from a posttest given to both experimental group and control group. The scores obtained were then analyzed by using two forms of statistical analysis; descriptive statistical analysis and inferential statistical analysis which were done by using two?way ANOVA and continued by Tukey test to find out the interactional effect between the teaching techniques applied and two text types. Kolmogorov-Smirnov statistics was applied to test the normality of the data distribution, whereby were normally distributed. Besides, Levene?s test of Equality of Error variance found that the variances of data were homogeneous. FINDINDS AND DISCUSSION This research tried to answer four research questions.The following description explains the finding that anwers each research question. The first research question is concerned with whether there is a significant difference in reading achievement between the students who are taught by using QAR technique and those taught by using DRTA technique. Inferential statistics finds that both the QAR technique and DRTA technique have an effect on students? reading achievement. The result of the analysis shows the coeficient of ANOVA as FAB = 51.9985. This measure is then compared to Fcv(3,136;(005)) = 2.675. From this difference calculation, it can be said that FAB was higher than Fcv. It means this difference calculation, the first research question is answered, that is, there is a significant difference in students? reading achivement between the students who are taught by using QAR technique and those taught by using DRTA technique. Moreover, the difference of the gain mean score indicates that QAR technique is more effective than DRTA technique. The difference of the gain mean score of the students? reading achievement who taught by using the QAR technique (XAI = 0.68) is higher than the gain mean score of the students? reading achievement who taught by using DRTA technique (XA2 = 0.31). The difference result above strongly believed that QAR technique is better than DRTA technique. Conner (2006) highlights that Question-Answer Relationship (QAR)) as a reading strategy in which students categorize comprehension question according to where they get information they need to answer each question. The students are asked to indicate whether the information they use to answer question about the text is textually explicit and implicit information. Conner adds his logical reasons for the strength points of the possibility in implementing the QAR in teaching reading in EFL teaching, that is, it helps the students figure out how to go about answering the questions based on a given text and it helps students understanding the different types of question and know to approach requires the students to analyze the types of question. Furthermore, Zygouris-Coe and Glass (2004) affirms that QAR technique helps students better understanding of the text learned. Moreover, Raphael (1986) defines Question-Answer Relationships, or QAR, is a reading comprehension strategy developed to clarify how students approach the tasks of reading texts and answering questions. It encourages students to be active, strategic readers of texts. Further Raphael discloses the reasons of implementing QAR in teaching reading comprehension; 1) question-answer relationship technique helps students learn the kind of thinking that different types of questions require, as well as where to go for answers in the text. It encourages students to be more efficient and strategic readers, 2) question-answer relationship can help students to ask effective questions as they read and respond to the text, 3) Teachers use QAR to guide and monitor student learning and to promote higher-level thinking in their students, and 4) question-answer relationship is an effective strategy for improving students? reading comprehension. Above experts? ideas are also in line with research conducted by Kinniburgh in 2010. He investigated the effect of QAR technique toward students? reading comprehension achievement primary grades students at University of South Alabama, College of Education, U.S.A and the research finding out that QAR is an effective technique to increase comprehension of young students and provide a strong foundation for reading comprehension. The second research question is whether or not significant interactional effect between techniques applied and two text types. The two-way ANOVA shows that the value of FAB on the interactional effect is 5.237, whereas Fcv(1,136;(005)) is 3.92 when Fob is higher than Fcv, it means that there is a significant interactional effect between the teaching techniques applied and two text types. Because there is an effect of the interaction in this research, third and fourth research questions could be continued. The third research question is whether there is a significant difference in reading achievement between the students who are taught by using QAR technique and those taught by using DRTA technique in descriptive text type. Inferential statistics shows that the gain mean score of students who are taught by using QAR technique in descriptive text type (XA1B1: 0.7297) is higher than the gain mean score of the students who are taught by using DRTA technique in descrptive text type (XA2B1: 0.5769). To ensure these means difference are significant, the Tukey test is also conducted. The Tukey test finds out that The Qcv on df = 35 at the significant value 0.05 is 2.035, whereas Qob is 2.376785. From the calculation, Qob> Qcv, indicates that significant means difference is answered. Fourth research question is whether there is a significant difference in reading achievement between the students who are taught by using QAR technique and those taught by using DRTA technique in narrative text type. Inferential statistics and Tukey test, which indicates that the gain mean score of the students? reading achievement who are taught by using QAR technique in narrative text type (A1B2: 0.5769) is higher than the gain mean score of the students? reading achievement who are taught by using DRTA technique in narrative text type (A2B2: 0.4534). Besides, the result of Tukey test finds out that the value of Qcv in df = 35 at the significance level 0.05 is 2.035, compared to the Qcv is 2.62 from this calculation, it indicates that Qob is higher than Qcv, which means there is a significant difference in the reading achievement between the students who are taught by using QAR technique and the students who are taught by using the DRTA technique in narrative text type. CONCLUSION, IMPLICATION, AND SUGGESTION Based on the data analysis presented, the conclusion of this study can be described as follows: 1) There was a significant difference in reading achievement of describing thing, culture and art, and communication & information technology of the tenth year students of Saraswati Senior High School Seririt in the academic year 2012/2013 between the students who were taught by using QAR technique and those taught by using DRTA technique in desriptive and narrative text types. The students? reading achievement was better when they were taught by using QAR technique than when they were taught by using DRTA technique both descriptive and narrative text types, 2) There was a significant interactional effect between the teaching techniques applied and text types toward their reading achievement of describing thing, culture and art, and communication & information technology of the tenth year students of Saraswati Senior High School Seririt in the academic year 2012/2013, 3) There was a significant difference in the reading achievement for the topics of describing thing, culture and art, and communication & information technology of the tenth year students of Saraswati Senior High School Seririt in the academic year 2012/2013 between the students who were taught by using QAR technique and those taught by using DRTA technique in descriptive text type. QAR technique gave better achievement to the students? reading competency than DRTA technique in descriptive text type, and 4) There was a significant difference in the reading achievement of describing thing, culture and art, and communication & information technology of the tenth year students of Saraswati Senior High School Seririt in the academic year 2012/2013 between the students who were taught by using QAR technique and those taught by using DRTA technique in narrative text type. QAR technique gave better achievement to the students? reading competency than DRTA technique in narrative text type. The implication of this study strongly indicated that the application of QAR technique is more effective than DRTA technique in descriptive and narrative text types for students? reading competency toward the topics of describing thing, culture and art, and communication & information technology of the tenth year students of Saraswati Senior High School Seririt in the academic year 2012/2013. The English teachers should consider to use the QAR technique as one of alternative techniques in teaching reading of descriptive and narrative text types since it was proven in this study. It indicated that the usage of QAR technique is one of the potential technique to support better students? competence in reading. Moreover, QAR technique is appropriate to be applied by English teachers for increasing students? reading competency in descriptive and narrative text types for senior high school level. Additionally, English teacher reconsider the implementation of DRTA technique in teaching reading for descriptive and narrative text types since it was not more effective than QAR technique. Based on the finding of the analysis and the implications, the researcher has one suggestion for the English teacher in SMA Saraswati Seririt in academic year 2012/2013 should use QAR technique to teach descriptive and narrative reading text type because QAR teachnique is able to encourage students to be active in reading class and QAR technique is also able to lead students to find out the main idea of the reading text easily. Furthermore, QAR technique is suggested to be applied since it involves activities that can support students? reading competency. Besides, the English teachers are also suggested to realize that QAR technique was more effective in upgrading students? reading achievement for two types of reading text only, that is, descriptive and narrative text types. . THANKS TO: Researcher would like to express her greatest acknowledge a number of people for the help given to her during the process of writing this thesis: 1) Prof. Dr. Nyoman Sudiana, M.Pd, as the Rector of Ganesha University of Education Singaraja, Indonesia and as my first supervisor for his guidance, criticism, attention to details, motivation and support, during the process of accomplishment of this research; 2) Prof. Dr. Nyoman Dantes, the Director of Postgraduate Program, for his valuable help, lessons, criticism, motivation and support; 3) Prof. Dr. I. Nengah Suandi, M.Hum, the Head of Language Education Program, for his attention, motivation and support; 4) Prof. Dr. I Nyoman Adi Jaya Putra, M.A., as my second supervisor for his valuable academic and non academic guidance, supervision, motivation and support during the whole process of this research accomplishment; 5) Drs. Nyoman Arjana, M.Pd for his recommendation to conduct this research at SMA Saraswati Seririt, 6) Agus Kadek Sutastrawan, M.Pd, as the English teacher for his valuable help, motivation and support during collecting the data of this study; 7) First year students of Saraswati Senior High School Seririt in the academic year 2012/2013, for their active participation during collecting the data of this thesis; 8) My classmates who have shared their academic inputs during finishing this study; 9) My beloved husband Putu Sunadia., for his valuable academic and non academic guidance, motivation and support during the whole process of my study; and My beloved daughters Putu Shela Widyawati and Kadek Nadia Sari, and my beloved son Komang Raditya Ray Wijaya for their motivation and warm greeting during the whole process of my study at Ganesha University of Education Singaraja, Indonesia. Finally, I realize that this research is still far from perfect. Therefore, any constructive suggestions and criticism are highly appreciated. REFERENCES Burgess, Debra. A. 1997. Directed Reading Thinking Activities. New York : Scholastic Books. http:/www. Marvbk.com./teachers.html. Accessed on January 24th 2010. Celce-Murcia, M. 2001. Teaching English as a Second or Foreign Language (Third Edition). New York: Heinle&Heinle, Ltd. Depdiknas. 2007. Materi Sosialisasi dan Pelatihan Kurikulum Tingkat Satuan Pendidikan (KTSP) SMK. Jakarta : Departemen Pendidikan Nasional. Dinnen, Frencis, P; SJ. 1967. General linguistic. USA: Holt Rinehart and Winston Inc. Harmer, J. 2007. How to (New Edition). Edinburgh Gate: Pearson Longman. Harper and Row. http://www.surgery.mc.duke.edu/commdis/clds. Accessed on February 1th 2010. Kinniburgh, H.L. 2010. Question-Answer Relationships (QAR) in the Primary Grades: Laying the Foundation for Reading Comprehension. University of South Alabama, College of Education, U.S.A. Koyan, W.I. 2011. Statistik Terapan. Singaraja: Program Pascasarjana Universitas Pendidikan Singaraja. Nunan, D. (1991b). Language Teaching Methodology. New York: Prentice Hall. Olson, Arthur V., and Ames, Wilbur S. 1972. Teaching Reading Skill in Second School. New York, Intex Education Publish. Paris, Scott G. 2005. ?Reinterpreting the development of reading skills?. Journal of Reading Research Quarterly Vol. 40, No. 2 April/May/June 2005. http://www.google.co.id/url?sa=t&rct=j&q=pdf. Accessed on 13 November 2012. Richards, Jack and Theodore Rodgers. 2002. Approaches and Methods in Language Teaching. (second Edition). Cambridge: Cambridge University Press. Stauffer, R.G. 1980. Directing Reading Maturity as a Cognitive Process. New York. Walker, Barbara J. 1992. Diagnostic Teaching Of Reading Technique for Instruction and Assessment. 2ndEd. New York : Macmillan. Walker, Barbara J. 2008. Diagnostic Teaching of Reading: Techniques for Instruction and Assessment (6thed). Ohio: Pearson Education Ltd. Zygouris-Coe, V. And Glass, C. 2004. Modified QAR. Last updated 6 December 2004. http://forpd.unf.edu./strategies/stratqar.html. Accessed on 19 September 2009. keyword : comparative, QAR, DRTA, reading achievement